SPICE simulation assisted-dynamic Rds(on) characterization in 200V commercial Schottky p- GaN HEMTs under unstable phases - Liu, Xinzhi; Shafie, Suhaidi; Amran Mohd Radzi, Mohd; Azis, Norhafiz (Institute of Physics, 2024)
This paper presents a comprehensive analysis of dynamic and static RDS(ON) in Schottky p-GaN High Electron Mobility Transistors (HEMTs), highlighting the impact of offstate and hot electron trapping on device performance. The authors observed significant hysteresis in the transfer characteristics of a 200V commercial Schottky p-GaN, attributing this to charge trapping effects. A novel experimental setup, employing a multi-pulse test synchronous buck converter circuit with additional gate control and a clamping circuit, enabled precise characterization of dynamic RDS(ON) under varying conditions, including unstable phases with overcurrent. This method effectively mimics solar PV input scenarios, exposing the device to high dv/dt and di/dt stresses, which are critical for evaluating GaN device stability under transient conditions. This research also reveals that increased gate resistance reduces energy losses, challenging traditional expectations by demonstrating the nuanced gate charge dynamics of GaN HEMTs. This study overall contributes to the understanding of GaN device behavior, offering a novel approach for accurately characterizing dynamic RDS(ON) under unstable stages, furtherly advances the GaN device in complex renewable energy power converter applications.